Characterization of genetic diversity of citron watermelon landrace accessions of South Africa through simple sequence repeat markers. Issue 3 (4th May 2023) - Ngwepe, Richard Mantlo; Shimelis, Hussein; Mashilo, Jacob; Shayanowako, Admire Isaac Tichafa
ABSTRACT: Profiling the genetic diversity of germplasm collections is fundamental for selection programs and strategic conservation. Citron watermelon ( Citrullus lanatus var. citroides [L.H. Bailey] Mansf. ex Greb.) is an under-researched cucurbit crop despite providing food and nutritional security in sub-Saharan Africa. There is limited information on genetic relationships of South African citron watermelon accessions for effective breeding. The objective of this study was to determine the extent of genetic diversity among 48 South African citron watermelon landrace accessions using selected simple sequence repeat (SSR) markers to identify genetically divergent accessions for trait integration and variety development. The SSR markers amplified a total of 24 alleles, with a mean expected heterozygosity value of 0.38, indicating moderate genetic diversity among the studied accessions. The mean polymorphic information content value of 0.21 indicated low discriminatory power of the SSR markers. Analysis of molecular variance attributed 8%, 75%, and 17% of the molecular variation between populations, among accessions and within accessions, respectively. Three distinctive genetic groups were identified based on cluster analysis, which aided the selection of genetically diverse citron watermelon accessions for breeding and cultivar development.